Quantification of Peroxide Ion Passage in Dentin, Enamel, and Cementum After Internal Bleaching With Hydrogen Peroxide - Palo, R. M. [UNESP]; Bonetti-Filho, I. [UNESP]; Valera, M. C. [UNESP]; Camargo, C. H. R. [UNESP]; Camargo, S. E. A. [UNESP]; Moura-Netto, C.; Pameijer, C. (Operative Dentistry Inc, 2012)
The aim of this study was to evaluate the amount of peroxide passage from the pulp chamber to the external enamel surface during the internal bleaching technique. Fifty bovine teeth were sectioned transversally 5 mm below the cemento-enamel junction (CEJ), and the remaining part of the root was sealed with a 2-mm layer of glass ionomer cement. The external surface of the samples was coated with nail varnish, with the exception of standardized circular areas (6-mm diameter) located on the enamel, exposed dentin, or cementum surface of the tooth. The teeth were divided into three experimental groups according to exposed areas close to the CEJ and into two control groups (n=10/group), as follows: GE, enamel exposure area; GC, cementum exposed area; GD, dentin exposed area; Negative control, no presence of internal bleaching agent and uncoated surface; and Positive control, pulp chamber filled with bleaching agent and external surface totally coated with nail varnish. The pulp chamber was filled with 35% hydrogen peroxide (Opalescence Endo, Ultradent). Each sample was placed inside of individual flasks with 1000 mu L of acetate buffer solution, 2 M (pH 4.5). After seven days, the buffer solution was transferred to a glass tube, in which 100 mu L of leuco-crystal violet and 50 mu L of horseradish peroxidase were added, producing a blue solution. The optical density of the blue solution was determined by spectrophotometer and converted into microgram equivalents of hydrogen peroxide. Data were submitted to Kruskal-Wallis and Dunn-Bonferroni tests (alpha=0.05). All experimental groups presented passage of peroxide to the external surface that was statistically different from that observed in the control groups. It was verified that the passage of peroxide was higher in GD than in GE (p<0.01). The GC group presented a significantly lower peroxide passage than did GD and GE (p<0.01). It can be concluded that the hydrogen peroxide placed into the pulp chamber passed through the dental hard tissues, reaching the external surface and the periodontal tissue. The cementum surface was less permeable than were the dentin and enamel surfaces.